Product Innovation Analysis as a Strategy to Survive in Competitive Markets - Zahara Meutia; Henny Purnama Dewi; Faziatul Amillia Mohamad Basir; Muammar Rinaldi; Azizul Kholis (Outline Publisher, 2024)
This study aims to analyze the role of product innovation as a strategy to survive in a competitive market. Product innovation is the main key for companies in facing tight competition in the era of globalization and rapid technological development. This study uses a quantitative descriptive method with a survey approach to small, medium, and large companies in several industrial sectors. Data were collected through questionnaires and in-depth interviews with company management who have experience in developing innovative products. The results of the study show that product innovation has a significant positive impact on the competitiveness and performance of the company, both in terms of increasing sales, customer loyalty, and market share. Factors that support the success of product innovation include the use of technology, research and development (R&D), and a focus on customer needs. In addition, obstacles that are often faced in implementing innovation include limited resources, capital, and access to technology. Proposed solutions include increasing investment in technology, collaboration with research institutions, and implementing customer-centric strategies.